A therapeutic confirmatory study to assess the safety and efficacy of Zydena (udenafil) for the treatment of erectile dysfunction in male patients with diabetes mellitus - Moon, Du Geon; Yang, Dae Yul; Lee, Choong Hyun; Ahn, Tai Young; Min, Kweon Sik; Park, Kwangsung; Park, Jong Kwan; Kim, Je Jong (Journal of sexual medicine, 2011)
Patients with diabetes mellitus (DM) are reported to experience more severe erectile dysfunction (ED) symptoms and respond less to ED treatments compared with patients with ED of other etiologies. This study was undertaken to evaluate the safety and efficacy of udenafil for the treatment of ED in a larger number of patients with DM. A placebo-controlled, randomized, double-blind, double-dummy, parallel-group design multicenter study, fixed-dose trial was conducted. The trial involved seven study sites in Korea, with 174 ED patients with DM. The subjects, treated with placebo, 100 mg, or 200 mg of udenafil for 12 weeks, were asked to complete the International Index of Erectile Function (IIEF), the Sexual Encounter Profile (SEP) diary, and the Global Assessment Question (GAQ) during the study period. The primary efficacy parameter was the change in the erectile function domain (EFD) score of IIEF from baseline. Secondary parameters were IIEF questions 3 (Q3) and Q4, SEP Q2 and Q3, rate of achieving normal erectile function (EFD ≥ 26), and the response to GAQ. Compared with the placebo, patients receiving both doses of udenafil showed statistically significant improvements in the IIEF-EFD score, respectively. However, statistically significant difference was not observed between the udenafil 100 mg and the udenafil 200 mg groups. Similar results were observed in the comparison of Q3 and Q4 of IIEF, SEP diary, and GAQ. The percentages of subjects experiencing at least one adverse event related to the study drugs were 3.6%, 15.8%, and 22.4% for the placebo, udenafil 100 mg, and udenafil 200 mg groups, respectively. However, these events were all mild in severity. Major adverse events were flushing, headache, nausea, and conjunctival hyperemia. Udenafil was significantly effective for the treatment of ED, demonstrating statistically significant improvement in erectile function in patients with DM. The incidence of adverse events was relatively low and well tolerated in patients with DM.